2012
DOI: 10.1016/j.physe.2012.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Nonlocal correlations for manifold quantum systems: Entanglement of two-spin states

Abstract: In this paper, we study the bipartite entanglement of spin coherent states in the case of pure and mixed states. By a proper choice of the subsystem spins, the entanglement for large class of quantum systems is investigated. We generalize the result to the case of bipartite mixed states using a simplified expression of concurrence in Wootters' measure of the bipartite entanglement. It is found that in some cases, the maximal entanglement of mixed states in the context of su(2) algebra can be detected. Our obse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…In order to find the entanglement entropy which is a nonlocal quantity [14], we first conduct bipartition. We can arbitrarily divide the space into two parts, A and B.…”
Section: Topological Entanglement Entropymentioning
confidence: 99%
“…In order to find the entanglement entropy which is a nonlocal quantity [14], we first conduct bipartition. We can arbitrarily divide the space into two parts, A and B.…”
Section: Topological Entanglement Entropymentioning
confidence: 99%
“…But for maximally entangled states (Bell states) these measures exhibit maximum values. Entanglement properties of some special quantum states like superposition of coherent states [4][5][6] and two-qubit Werner states have been investigated [7].Recent studies have demonstrated that quantum systems in higher dimensions may improve the efficiency of quantum information protocols, security of quantum cryptography, and quantum channel capacities [8][9][10][11][12].Because higher dimensional entangled states allow the realization of new types with higher capacity of quantum communication protocols [13].…”
Section: Introductionmentioning
confidence: 99%
“…Also, it has been used in other important applications such as superdense coding [5] and quantum metrology [6]. Several entanglement measures such as concurrence [7], entanglement of formation [8], tangle [9] and negativity [10] have been proposed in pure and mixed states. In this regard, the concurrence and negativity are used as entanglement measures for a mixed state, but for a pure state, the von Neumann entropy of density matrix can also be used as a measure of entanglement [11].…”
Section: Introductionmentioning
confidence: 99%